(untitled) (Ameghiniana, 2014)
Cenozoic sediments from the well Cx-1 of offshore Colorado Basin were studied. The dinoflagellate cysts assemblages are diverse and well preserved providing stratigraphic control for the section. Selected dinoflagellate cyst last occurrences or abundance events suggest seven age intervals: Maastrichtian, Paleocene, Late Eocene to Early Oligocene, Late Oligocene to Early Miocene, Mid Miocene, Late Miocene and Late Miocene to Early Pliocene. These results are compared with previous studies, carried out by other authors exhibiting a consistent succession of events throughout the basin. Qualitative and quantitative dinoflagellate cyst data allow the recognition of apparent sea level changes. Sediments ranging frorn Maastrichtian to Selandian in age show a gradual rise in sea leve!. These assemblages bear both gonyaulacacean and peridiniacean dinoflagellate cysts suggesting open marine conditions with a marked fall in sea level at the top of this interval. Sediments interpreted as Late Eocene to Early Oligocene in age were deposited in a more open marine environment. At the Early Oligocene/Late Oligocene boundary a second low see level episode occurred. Throughout the Late Oligocene to Early Miocene and Mid to Late Miocene intervals high dinocyst abundances and the presence of oceanic species suggest a sea level highstand. Upwards the dominance of terrestrially derived palynomorphs as well as the scarcity of dinoflagellate cysts indicate nearshore depositional environments at the end of the Miocene-Early Pliocene.